2016
DOI: 10.3390/nu8050304
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gestational and Lactational Age on the Human Milk Metabolome

Abstract: Human milk is the ideal nutrition source for healthy infants during the first six months of life and a detailed characterisation of the composition of milk from mothers that deliver prematurely (<37 weeks gestation), and of how human milk changes during lactation, would benefit our understanding of the nutritional requirements of premature infants. Individual milk samples from mothers delivering prematurely and at term were collected. The human milk metabolome, established by nuclear magnetic resonance (NMR) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
139
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(160 citation statements)
references
References 52 publications
14
139
2
5
Order By: Relevance
“…Thus, the finding of both betaine and choline and its derivatives in colostrum of preterm neonates in the study of Sundekilde et al [36], as well as the discovery of an increase of glycerophosphocholine in the first 3 months of lactation highlighted by Andreas et al [37], support the hypothesis of the importance of these 2 metabolites for the survival and growth of preterm neonates. In a recent study by Marincola et al [4] an age-dependent modification of the urine metabolome was observed in term neonates, mainly characterized by similar temporal trends of choline and betaine.…”
Section: Choline and Betainementioning
confidence: 72%
“…Thus, the finding of both betaine and choline and its derivatives in colostrum of preterm neonates in the study of Sundekilde et al [36], as well as the discovery of an increase of glycerophosphocholine in the first 3 months of lactation highlighted by Andreas et al [37], support the hypothesis of the importance of these 2 metabolites for the survival and growth of preterm neonates. In a recent study by Marincola et al [4] an age-dependent modification of the urine metabolome was observed in term neonates, mainly characterized by similar temporal trends of choline and betaine.…”
Section: Choline and Betainementioning
confidence: 72%
“…With most compounds having hydrogen, ¹H-NMR provides a robust approach in the detection and identification of various metabolites (Savorani et al, 2013), thus several BM metabolomic studies have employed this technique (Smilowitz et al, 2013;Praticò et al, 2016;Longini et al, 2014;Sundekilde et al, 2016;Wu et al, 2016). Unlike MS-based techniques, NMR is nondestructive allowing preservation of metabolites for multiple analysis (Ryan et al, 2013).…”
Section: Instrumentations Used In Breastmilk Metabolomicsmentioning
confidence: 99%
“…One of the strengths of NMR-based metabolomics is that it can provide structural and quantitative information on the metabolite which facilitates identification of unknown metabolites, a major hurdle in metabolomics (Brennan, 2016). A major drawback of NMR-based techniques is the lack of sensitivity making detection of low abundance metabolites difficult (Brennan, 2016;Sundekilde et al, 2016).…”
Section: Instrumentations Used In Breastmilk Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, existem diferenças específicas e significativas entre o leite das mães de prematuros e de bebês a termo (GROSS et al, 1980;BOBINSKI et al, 2013;SUNDEKILDE et al, 2016). A produção de leite materno é altamente sensível às necessidades específicas do filho RN (GROSS et al, 1980;BOBINSKI et al, 2013), sugerindo que a composição do leite materno pode ser fortemente moldada pela idade gestacional e peso do neonato (BOBINSKI et al, 2013).…”
Section: A Importância Do Ame Para Os Prematurosunclassified